Hadith About Charity: Implementation and Its Impact on Social Welfare in the Charity Foundation (LAZISMU) in Southeast Aceh Regency - Nisak, Khoirun; Siregar, Muhammad Nuh (JASNA : Journal For Aswaja Studies, 2025)
The concept of charity in Islamic teachings has a very broad scope, not limited to material or non-material donations. In the Quran, the term “shadaqah” represents all forms of charitable deeds, including non-material actions of a social and moral nature, such as removing hazards from the road, guiding people with disabilities, spreading smiles, and other positive behaviors toward others. This study aims to investigate how the implementation and impact of zakat institutions (Lazismu) contribute to improving the well-being of communities in Southeast Aceh, by examining hadiths related to charity.This study uses a quantitative method with field research. Data was collected from primary and secondary sources. Primary data was obtained from interviews and data collected during distribution and charity activities. Primary data sources include the Sunan An-Nasai, Sahih Bukhari, and the latest scientific studies. The results of this study indicate the level of influence of charity at the Lazismu Aceh Tenggara institution on community welfare as follows: in 2022, charity funds had an influence of approximately 6.23%, in 2023 the influence of charity was approximately 6.16%, in 2024, the influence was very high at around 12.24%, and finally, from January to March 2025, the influence of charity at Lazismu Aceh Tenggara reached 3.86%.